KESAKSIAN PENYIDIK DALAM PEMBUKTIAN PERKARA PIDANA (STUDI KASUS : PUTUSAN NO. 1273/PID.B/2013/PN.JKT.SEL) - Ariadi Hanta Wijaya; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2018)
In the context of criminal law, proof is the core of criminal proceedings because what is sought in criminal law is material truth. Basically, this aspect of proof has actually begun at the stage of criminal investigation. The act of investigation and investigation will be carried out immediately in the event of a criminal offense, the existence of a criminal offense can be known by the officer, with reports, complaints, caught red-handed, or known directly by the officer. So, before an act of investigation is carried out, an investigation is carried out by an investigating official, with the intention and purpose of finding and finding an event that is investigated a criminal event or not, if the investigation results as a criminal event, an investigation can be carried out. or certain civil servants who are authorized to carry out investigations, before the investigator conducts investigations such as making arrests, calling, searching, detaining, confiscating, the investigator must notify the public prosecutor so that the prosecutor can follow his investigation from the beginning, and if deemed necessary to give instructions in order to perfect the investigation. In the murder case with the defendant Andro and Benges, the witnesses presented by the Public Prosecutors in the trial were almost all investigators who examined this case. If only an investigator is present in proving someone guilty or not in a criminal case, of course the investigator will justify what he has done so that his statement becomes not objective.